Conduction band position tuning and Ga-doping in (Cd, Zn)S alloy thin films. (20th February 2017) - Baranowski, Lauryn L.; Christensen, Steven; Welch, Adam W.; Lany, Stephan; Young, Matthew; Toberer, Eric S.; Zakutayev, Andriy
Abstract : We used experiment and theory to explore alternative contact layers for accelerating the implementation of new photovoltaic absorber materials. Abstract : In recent years, the number of novel photovoltaic absorber materials under exploration has rapidly increased. However, to reap the most benefit from these new absorbers, alternative device structures and components must also be considered. In particular, the choice of a heterojunction partner, or contact layer, is critical to device optimization. In this work, we explore alternative n-type contact layer candidates that could be widely applicable to a variety of new absorbers. We use theory to calculate the band edge tuning provided by a variety of II–VI alloy systems, and select the (Cd, Zn)S system as one that affords a wide range of conduction band tuning. The synthesis of (Cd, Zn)S alloys is explored using atomic layer deposition, which afforded precise compositional control and produced crystalline thin films. The predicted tuning of the band gap and conduction band minimum is confirmed through X-ray photoelectron spectroscopy and optical absorption measurements. In addition, we investigated Ga-doping in Cd0.6 Zn0.4 S films to decrease their series resistance when used as contact layers in photovoltaic devices. This study provides a framework for exploring and optimizing alternative contact layer materials, which will prove critical to the success of new PV absorbers.